«I Jornades catalanes sobre Llengües per a Finalitats Específiques. Actes ». (1998) - Helena Aguilà (Swervei de publicacions, 1999)
I Jornades catalanes sobre Llengües per a Finalitats Específiques. Actes. (1998)